Did early shifts to bird pollination impose constraints on Salvia flower evolution?. (8th December 2022) - Sazatornil, Federico; Fornoni, Juan; Fragoso-Martínez, Itzi; Pérez-Ishiwara, Rubén; Benitez-Vieyra, Santiago
Abstract: A recent article by Kriebel et al. (2020) examines the relationship between floral shape evolution and pollination shifts in Salvia, a plant genus almost worldwide distributed, but particularly diverse in the New World. Kriebel et al. (2020) argue that a major shift to bird pollination at the origin of the subg. Calosphace ( 20 million years ago [Mya]) imposed a legacy of constraints, resulting in significant differences in flower morphology between New World and Old World Salvia . However, reanalyses of the data using hidden states to account for the heterogeneity in evolutionary rates do not support an early origin of bird pollination in this group. Instead, bird pollination may have appeared after the arrival of modern hummingbirds to North America (15.5–12 Mya), as in other North American plant clades. The use of more complex models of ancestral state reconstruction into comparative analyses provides a different perspective to explain morphological differences within Salvia. Our results indicate that bird pollination did not impose constraints on corolla shape evolution. Evolutionary constraints in anther connective and style shapes may have arisen at the origin of Calosphace but they were not associated with shifts to hummingbird pollination, being more likely the product of contingent evolution.